Association between cardiorespiratory fitness and body fat in girls - Minatto, Giseli (Rev Paul Pediatr, 2016)
OBJECTIVE: To estimate the prevalence of low cardiorespiratory fitness and its association with excess body fat, considering the sexual maturation and economic level in female adolescents. METHODS: Cross-sectional, epidemiological study of 1223 adolescents (10-17 years) from the public school system of Cascavel, PR, Brazil, in 2006. We analyzed the self-assessed sexual maturation level (prepubertal, pubertal and post-pubertal), the economic level (high and low) through a questionnaire and body fat (normal and high) through triceps and subscapular skinfolds. The 20-meter back-and-forth test was applied to estimate maximum oxygen consumption. Cardiorespiratory fitness was assessed according to reference criteria and considered low when the minimum health criterion for age and sex was not met. Chi-square test and logistic regression were applied, with a significance level of 5%. RESULTS: The prevalence of low cardiorespiratory fitness was 51.3%, being associated with all study variables (p<0.001). At the crude analysis, adolescents with high body fat were associated with low cardiorespiratory fitness, when compared to those with normal body fat (OR=2.76; 95%CI: 2.17-3.52). After adjustment by sexual maturation, this association remained valid and showed an effect that was 1.8-fold higher (95%CI: 1.39-2.46) and after adjusting by economic level, the effect was 1.9-fold higher (95%CI: 1.45-2.61). CONCLUSIONS: Approximately half of the assessed girls showed unsatisfactory levels of cardiorespiratory fitness for health, which was associated with high body fat, regardless of sexual maturation level and economic level. Effective public health measures are needed, with particular attention to high-risk groups.